Impact of Treatment with Direct Acting Antiviral Drugs on Glycemic Control in Patients with Hepatitis C and Diabetes Mellitus. (13th January 2020) - Mada, Pradeep Kumar; Malus, Matthew E.; Parvathaneni, Arvin; Chen, Bing; Castano, Gabriel; Adley, Sharon; Moore, Maureen; Hieda, Michinari; Alam, Mohammed J.; Feldman, Mark; King, John William
Abstract : Aim . To assess the effect of treating chronic hepatitis C virus (HCV) infection with direct acting antiviral drugs (DAAs) on glycemic control in patients with concomitant diabetes mellitus (DM). Methods . We performed a retrospective case-control study in a viral hepatitis ambulatory clinic in Shreveport, Louisiana, during the period 11/01/2014 to 12/31/2017. All the clinic patient ages 18 years and above with treatment-naïve/biopsy-proven chronic hepatitis C and DM (hemoglobin   A 1 C   level ≥ 6.5 % ) who were eligible for treatment were included in the study. Of 118 such patients, 59 were treated with oral DAAs for 8-12 weeks with the goal of achieving a sustained virologic response (SVR). A control group of 59 patients did not receive treatment for their hepatitis C and was followed in the clinic. Patients in the control group did not receive treatment either due to insurance issues or refusal of hepatitis C treatment. Results . Fifty-five of the 59 patients treated with DAAs (93%) achieved a SVR. Six months after treatment completion, their mean ± SEM HbA1C level had decreased by 1.1 ± 0.03 % (P < 0.0001 ). Four of the 59 patients treated with DAAs did not achieve a SVR. Their mean HbA1C 6 months after treatment completion had increased by 0.8 ± 0.2 % . Furthermore, there was no improvement in HbA1C levels over time in the untreated group (mean HbA1C increase, 0.2 ± 0.05 % ; P < 0.0001 vs. the treatment group, which had a mean HbA1C decrease of 0.9 ± 0.2 % ). Conclusion . This controlled study demonstrated that treatment of chronic hepatitis C with DAAs results in statistically significant and meaningful reductions in hemoglobin A1C levels in patients with coexisting diabetic mellitus if a SVR is achieved.